Kemampuan Siswa dalam Menganalisis Struktur dan Kebahasaan Teks Ceramah - Karlina, Lis; Sukenti, Desi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This study aims to analyze students' abilities in analyzing the structure and language of lecture texts at SMK Negeri 1 Pangkalan Lesung. This research was conducted within the scope of the study of education, especially learning Indonesian, especially reading and writing. This research is a field research that uses a quantitative approach and descriptive method. The results of data analysis show three important things. First, in general, the ability to analyze the structure of lecture texts in class XI students of SMK Negeri 1 Pangkalan Lesung is very good with a score of 92.2. Second, in general, the ability to analyze the language of lecture texts in class XI students of SMK Negeri 1 Pangkalan Lesung is quite adequate with a score of 59.5. Thus, it is concluded that students have good abilities in analyzing the structure of lecture texts but still need to improve their abilities in analyzing the language of lecture texts. The results of this study are expected to contribute to the development of Indonesian language learning in schools and to provide useful information for teachers and other education stakeholders in improving students' ability to read and analyze lecture texts.